Sulfur-Doped Nanographenes Containing Multiple Subhelicenes - Niu, Wenhui; Fu, Yubin; Komber, Hartmut; Ma, Ji; Feng, Xinliang; Mai, Yiyong; Liu, Junzhi (Organic Letters, 2021)
In this work, we describe the synthesis and characterization of three novel sulfur-doped nanographenes (NGs) (1-3) containing multiple subhelicenes, including carbo[4]helicenes, thieno[4]helicenes, carbo[5]helicenes, and thieno[5]helicenes. Density functional theory calculations reveal that the helicene substructures in 1-3 possess dihedral angles from 15° to 34°. The optical energy gaps of 1-3 are estimated to be 2.67, 2.45, and 2.30 eV, respectively. These three sulfur-doped NGs show enlarged energy gaps compared to those of their pristine carbon analogues.
CRIS-Team Scopus Importer:2023-03-20